Answer:
<h2>(f + g)(x) = x² + 3x - 5</h2>
Step-by-step explanation:
![(f+g)(x)=f(x)+g(x)\\\\f(x)=3x+1;\ g(x)=x^2-6\\\\(f+g)(x)=(3x+1)+(x^2-6)=x^2+3x+1-6=x^2+3x-5](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3Df%28x%29%2Bg%28x%29%5C%5C%5C%5Cf%28x%29%3D3x%2B1%3B%5C%20g%28x%29%3Dx%5E2-6%5C%5C%5C%5C%28f%2Bg%29%28x%29%3D%283x%2B1%29%2B%28x%5E2-6%29%3Dx%5E2%2B3x%2B1-6%3Dx%5E2%2B3x-5)
Answer:
Just do scan and solve by brainly really helpful ngl
Step-by-step explanation:
Answer:
238
Step-by-step explanation:
238.964286
Answer:
£78.4
Step-by-step explanation:
Since he earns £9.80 per hour, we multiply this by how many hours there are. So £9.80 times 8 is £78.4. I hope this helps!
In order they are
1.1 * 10^12, 9.5 * 10^11 and 5*10^8